Ancaman Fraud di Balik Digitalisasi: Seberapa Siap UMKM dengan Pengendalian Internal dan Literasi Digital - Iva Sofi Gunawati; Muhamad Nukha Murtadlo; Erni Harlina Isdiati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The rapid development of digital technology has transformed the operational activities of Micro, Small, and Medium Enterprises (MSMEs), while simultaneously increasing the risk of fraud. Therefore, effective internal control and adequate digital literacy are essential to mitigate fraud risks. This study aims to examine the influence of internal control and digital literacy on fraud prevention among MSMEs in Boyolali Regency, Indonesia. A quantitative research approach with a survey method was employed. Data were collected through questionnaires distributed to 100 MSME owners selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS software. The results indicate that internal control has a positive and significant effect on fraud prevention, with a significance value of 0.003 (p < 0.05). Digital literacy also has a positive and significant effect on fraud prevention, with a significance value of 0.000 (p < 0.05). Simultaneously, internal control and digital literacy significantly influence fraud prevention, as indicated by an F-test significance value of 0.000, and explain 63.0% of the variance in fraud prevention (R² = 0.630). These findings suggest that strengthening internal control systems, supported by improved digital literacy, is an effective strategy for enhancing fraud prevention among MSMEs in the era of digital transformation.